Controlling process performance indicators. Results of empirical and theoretical research = Wskaźniki dokonań controllingu. Ujęcie teoretyczne oraz wyniki badań empirycznych - Nowosielski, Krzysztof (Zielona Góra: Faculty of Economics and Management Press)
The article sheds light on the issue of controlling performance measurement on the basis of the available literature and empirical research conducted by the author. Sample indicators have been which can be used to confirm the efficiency of using controlling in a company as well as to determine the steps of its improvement and development.
Keywords: controlling process; pomiar; efektywność; skuteczność; wskaźniki dokonań; measurement; efficiency; effectiveness; performance indicators